Granite weathered residual land polymer solidification muck compaction segment and manufacturing method thereof

By using granite weathered residual land polymer to cure the slag compact sections, the problems of high demand for cement and gravel for precast concrete components and low absorption capacity of engineering slag are solved, and efficient resource utilization and building structure stability are achieved.

CN119912204AActive Publication Date: 2025-05-02GUANGZHOU MARITIME INST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510102497.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Conventional precast concrete components have a high demand for cement and natural sand and gravel, and my country's ability to absorb engineering slag is relatively low.

Method used

The compacted segments are compacted by granite weathered residual soil polymer. The raw material composition includes thermally activated modified granite weathered residual soil residue, sodium silicate, deionized water and engineering residue, and compacted segments are formed through a specific preparation process.

Benefits of technology

It achieves fast segmental condensation speed, excellent unlimited compressive strength and high water stability, reduces dependence on traditional cement and natural sand and gravel, promotes the recycling of engineering slag, and reduces the pressure of resource shortage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912204A_ABST
    Figure CN119912204A_ABST
Patent Text Reader

Abstract

The invention discloses a granite weathered residual soil polymer solidified muck compaction segment and a manufacturing method thereof. The segment is prepared from the following raw materials in percentage by mass: 5.26%-8.31% of thermally activated modified granite weathered residual soil residual mud, 1.21%-2.86% of sodium silicate, 4.26%-8.18% of deionized water and 80.98%-89.15% of engineering muck. The section is formed by uniformly stirring granite weathered residual land polymer neat paste and engineering muck, compacting and maintaining. When the section is used for preparing a precast concrete member, the use amount of post-cast new concrete can be greatly reduced, so that the use amount of cement and natural gravel required for preparing the new concrete is greatly reduced, and the section has relatively high economic and environment-friendly benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to resource utilization of engineering slag and prefabricated concrete components, and in particular to a compacted segment of granite weathered residual soil aggregate solidification slag and a manufacturing method thereof. Background Art

[0002] Precast concrete components have the advantages of fast construction speed, high product quality, and low labor demand on the construction site, and have been widely used in my country in recent years. However, conventional precast concrete components require a large amount of new concrete, and the demand for cement, sand and gravel is very high, which directly increases the carbon emissions of the building materials industry.

[0003] In recent years, with the development of urbanization in my country, more and more construction waste soil has been generated due to foundation pit excavation, tunneling and dredging projects. However, my country's capacity to absorb construction waste soil is relatively low. The open-air dumping of untreated construction waste soil not only occupies a large amount of land, but may also cause major safety accidents due to landslides. If construction waste soil can be used to replace part of the new concrete required for precast concrete components, the amount of cement and natural sand and gravel related to it will be greatly reduced, and the construction waste soil can be recycled, with obvious environmental protection and economic effects.

[0004] China's invention patent CN115627877B discloses a "steel tube concrete column with built-in compacted cement soil segment and its construction method". The patent document mixes cement and engineering slag and fills them into the pipe, and compacts them to form a compacted cement soil segment, which is used to replace new concrete to prepare steel tube concrete columns. Although the compacted cement soil segment can realize the consumption of engineering slag and save the amount of natural sand and gravel, it still requires cement and pipes during its preparation, and the energy consumption, carbon emissions and cost are all high, which is not conducive to engineering application. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a granite weathering residual soil polymer solidified slag compaction segment and a manufacturing method thereof, so as to solve the problem that conventional precast concrete components have high requirements for cement and sand and gravel and my country's relatively low capacity to absorb engineering slag.

[0006] Based on the above purpose, the present invention provides a granite weathered residual soil polymer solidified slag compaction segment, the raw material composition and mass percentage of which are: thermally activated modified granite weathered residual soil mud accounts for 5.26%-8.31%, sodium silicate accounts for 1.21%-2.86%, deionized water accounts for 4.26%-8.18%, and engineering slag accounts for 80.98%-89.15%;

[0007] The specific preparation method of the thermally activated modified granite weathered residual soil and mud is as follows:

[0008] S1. Add the residual soil and mud of weathered granite into a ball mill and grind at 40-60rpm for 4-6h to obtain fine weathered granite residual soil and mud;

[0009] S2. Add nanocellulose to deionized water and stir for 30-50 min, then add ammonium persulfate, heat to 50-60 ° C and stir for 2-4 h, centrifuge, wash and dry to obtain carboxylated nanocellulose;

[0010] S3. Add polyvinyl alcohol, carboxylated nanocellulose and 3-methyl-15-phenylpentadecanoic acid into deionized water and stir for 30-50 minutes, add a catalyst, heat to 60-80°C with stirring, react for 6-8 hours, adjust the pH to neutral, filter, wash and dry to obtain modified polyvinyl alcohol.

[0011] S4. The refined granite weathering residual soil mud obtained in step S1 is heated to 700-900° C. at a rate of 5-15° C. / min, kept warm for 1-3 hours, and then cooled to room temperature to obtain heat-activated granite weathering residual soil mud.

[0012] S5. Add the modified polyvinyl alcohol obtained in step S3 to deionized water, stir for 30-50 minutes, add the thermally activated granite weathering residual soil mud obtained in step S4, stir for 3-5 hours, and obtain thermally activated modified granite weathering residual soil mud.

[0013] Preferably, the solidified soil compaction segment is in the shape of a cylinder or a prism.

[0014] Preferably, the sodium silicate is a sodium silicate having a modulus of 0.9-1.5.

[0015] Preferably, the construction waste soil is waste soil excavated from underground construction with a particle size not exceeding 4.75 mm.

[0016] Preferably, the granite weathered residual soil and mud in step S1 are particles with a particle size not exceeding 0.15 mm in the granite weathered residual soil excavated during underground engineering construction.

[0017] Preferably, in step S2, the weight ratio of nanocellulose, ammonium persulfate and deionized water is 0.5-1:0.05-0.1:5-8.

[0018] Preferably, in step S3, the weight ratio of polyvinyl alcohol, carboxylated nanocellulose, 3-methyl-15-phenylpentadecanoic acid and deionized water is 0.8-1.2:0.4-0.6:0.4-0.6:3.2-7.2.

[0019] Preferably, the catalyst in step S3 is sulfuric acid with a concentration of 98%.

[0020] Preferably, in step S5, the weight ratio of the modified polyvinyl alcohol, deionized water and thermally activated granite weathered residual soil and mud is 0.25-0.8:1-2.4:5-8.

[0021] Furthermore, the present invention also provides a method for manufacturing the above-mentioned granite weathered residual soil aggregate solidified slag compaction segment, comprising the following steps:

[0022] 1. After adding sodium silicate to deionized water, pour in the thermally activated modified granite weathering residual soil and mud and stir for 20-30 minutes to obtain the granite weathering residual soil polymer slurry;

[0023] 2. Add construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 20-30 minutes to obtain loose slag slurry;

[0024] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device, the pressure value is 65-75MPa, and the pressure is maintained for 10-30min;

[0025] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 17-23° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathering residual soil polymer solidified slag.

[0026] Beneficial effects of the present invention:

[0027] 1. The segments prepared by the present invention have fast setting speed, excellent unconfined compressive strength and high water stability. Through the synergistic effect of specific raw material combination and preparation process, such as thermally activated modified granite weathered residual soil and mud, etc., it can achieve high strength in a short time, can quickly meet the requirements of engineering construction progress, enhance the stability of building structure, and ensure engineering quality.

[0028] 2. Make full use of construction waste and use it as one of the main raw materials, which greatly reduces the dependence on traditional cement and natural sand and gravel. Under the current situation of increasing amount of construction waste in my country and insufficient consumption capacity, it realizes the recycling of resources, alleviates the pressure of resource shortage, and provides an effective way for sustainable development.

[0029] 3. The present invention utilizes a steel mold as a preparation tool, which has a relatively high strength and allows a greater pressure to be used to compact the slag slurry, which is beneficial to improving the strength of the solidified slag compaction segment. When compacting the slag slurry, a certain holding time is maintained until the slag slurry solidifies. Therefore, the solidified slag compaction segment has a certain strength after demolding and can be used alone without the need for pipes, thereby reducing the cost of the segment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of manufacturing the compacted segment of the granite weathering residual soil aggregate solidification according to the present invention. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0032] Example 1: The specific preparation method of thermally activated modified granite weathered residual soil and mud is as follows:

[0033] S1. 1 kg of granite weathered residual soil was added to a ball mill and ground at 40 rpm for 4 h to obtain fine granite weathered residual soil;

[0034] S2. 50 g of nanocellulose was added to 500 g of deionized water and stirred for 30 min, then 5 g of ammonium persulfate was added, the temperature was raised to 50 ° C and stirred for 2 h, then centrifuged, washed and dried to obtain carboxylated nanocellulose;

[0035] S3. Add 50g of polyvinyl alcohol, 25g of carboxylated nanocellulose and 25g of 3-methyl-15-phenylpentadecanoic acid to 200g of deionized water and stir for 30min, add 1.5g of 98% sulfuric acid, heat to 60°C with stirring, react for 6h, adjust the pH to neutral, filter, wash and dry to obtain modified polyvinyl alcohol.

[0036] S4. 1 kg of the refined granite weathering residual soil mud obtained in step S1 is heated to 700° C. at a rate of 5° C. / min, kept warm for 1 hour, and then cooled to room temperature to obtain heat-activated granite weathering residual soil mud.

[0037] S5. Add 50 g of modified polyvinyl alcohol obtained in step S3 to 50 g of deionized water, stir for 30 min, add 1 kg of thermally activated granite weathering residual soil mud obtained in step S4, stir for 3 h, and obtain thermally activated modified granite weathering residual soil mud.

[0038] The specific preparation process of a compacted segment of granite weathered residual soil aggregate solidification is as follows:

[0039] 1. After adding 121g of sodium silicate to 443g of deionized water, pour in 526g of thermally activated modified granite weathered residual soil and stir for 20min to obtain a granite weathered residual soil polymer slurry;

[0040] 2. Add 8.91 kg of construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 20 minutes to obtain loose slag slurry;

[0041] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device with a pressure value of 65 MPa, and the pressure is maintained for 10 minutes;

[0042] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 17° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathering residual soil polymer solidified slag.

[0043] Example 2: The specific preparation method of thermally activated modified granite weathered residual soil and mud is as follows:

[0044] S1. Add 1 kg of granite weathering residual soil and mud into a ball mill and grind at 50 rpm for 5 h to obtain fine granite weathering residual soil and mud;

[0045] S2. 40 g of nanocellulose was added to 346.5 g of deionized water and stirred for 40 min, then 4 g of ammonium persulfate was added, the temperature was raised to 55 ° C and stirred for 3 h, then centrifuged, washed and dried to obtain carboxylated nanocellulose;

[0046] S3. 77 g of polyvinyl alcohol, 38.5 g of carboxylated nanocellulose and 38.5 g of 3-methyl-15-phenylpentadecanoic acid were added to 385 g of deionized water and stirred for 40 min, 2.3 g of 98% sulfuric acid was added, the temperature was raised to 70° C. with stirring, the reaction was performed for 7 h, the pH was adjusted to neutral, the mixture was filtered, washed and dried to obtain modified polyvinyl alcohol.

[0047] S4. 1 kg of the refined granite weathering residual soil mud obtained in step S1 is heated to 800° C. at a rate of 10° C. / min, kept warm for 2 hours, and then cooled to room temperature to obtain thermally activated granite weathering residual soil mud.

[0048] S5. Add 77g of modified polyvinyl alcohol obtained in step S3 to 230g of deionized water, stir for 40min, add 1Kg of thermally activated granite weathering residual soil mud obtained in step S4, stir for 4h, and obtain thermally activated modified granite weathering residual soil mud.

[0049] The specific preparation process of a compacted segment of granite weathered residual soil aggregate solidification is as follows:

[0050] 1. Add 200g of sodium silicate to 600g of deionized water, then pour in 700g of thermally activated modified granite weathered residual soil and stir for 25min to obtain a granite weathered residual soil polymer slurry;

[0051] 2. Add 8.5 kg of construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 25 minutes to obtain loose slag slurry;

[0052] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device with a pressure value of 70 MPa and the pressure is maintained for 20 minutes;

[0053] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 20° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathered residual soil polymer solidified slag.

[0054] Example 3: The specific preparation method of thermally activated modified granite weathered residual soil and mud is as follows:

[0055] S1. Add 1 kg of granite weathering residual soil and mud into a ball mill and grind at 60 rpm for 6 hours to obtain fine granite weathering residual soil and mud;

[0056] S2. 50 g of nanocellulose was added to 400 g of deionized water and stirred for 50 min, then 5 g of ammonium persulfate was added, the temperature was raised to 60 ° C and stirred for 4 h, then centrifuged, washed and dried to obtain carboxylated nanocellulose;

[0057] S3. 100 g of polyvinyl alcohol, 50 g of carboxylated nanocellulose and 50 g of 3-methyl-15-phenylpentadecanoic acid were added to 600 g of deionized water and stirred for 50 min, 3 g of 98% sulfuric acid was added, the temperature was raised to 80 ° C with stirring, the reaction was carried out for 8 h, the pH was adjusted to neutral, filtered, washed and dried to obtain modified polyvinyl alcohol.

[0058] S4. 1 kg of the refined granite weathering residual soil mud obtained in step S1 is heated to 900° C. at a rate of 15° C. / min, kept warm for 3 hours, and then cooled to room temperature to obtain heat-activated granite weathering residual soil mud.

[0059] S5. Add 100 g of modified polyvinyl alcohol obtained in step S3 to 250 g of deionized water, stir for 50 min, add 1 kg of thermally activated granite weathering residual soil mud obtained in step S4, stir for 5 h, and obtain thermally activated modified granite weathering residual soil mud.

[0060] The specific preparation process of a compacted segment of granite weathered residual soil aggregate solidification is as follows:

[0061] 1. After adding 286g of sodium silicate to 783g of deionized water, pour in 831g of thermally activated modified granite weathered residual soil and stir for 30min to obtain a granite weathered residual soil polymer slurry;

[0062] 2. Add 8.1 kg of construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 30 minutes to obtain loose slag slurry;

[0063] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device with a pressure value of 75 MPa and the pressure is maintained for 30 minutes;

[0064] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 23° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathering residual soil polymer solidified slag.

[0065] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that carboxylated nanocellulose is replaced with nanocellulose, and the specific preparation process is as follows: The specific preparation method of thermally activated modified granite weathering residual soil and mud is as follows:

[0066] S1. Add 1 kg of granite weathering residual soil and mud into a ball mill and grind at 50 rpm for 5 h to obtain fine granite weathering residual soil and mud;

[0067] S2. 1 kg of the refined granite weathering residual soil mud obtained in step S1 is heated to 800° C. at a rate of 10° C. / min, kept warm for 2 hours, and then cooled to room temperature to obtain thermally activated granite weathering residual soil mud.

[0068] S3. Add 77g of polyvinyl alcohol and 38.5g of 3-methyl-15-phenylpentadecanoic acid to 385g of deionized water and stir for 40min, add 2.3g of 98% sulfuric acid, heat to 70°C with stirring, react for 7h, adjust the pH to neutral, filter, wash and dry to obtain modified polyvinyl alcohol.

[0069] S4. Add 39 g of modified polyvinyl alcohol and 39 g of nanocellulose to 230 g of deionized water, stir for 40 min, add 1 kg of thermally activated granite weathering residual soil mud obtained in step S2, stir for 4 h, and obtain thermally activated modified granite weathering residual soil mud.

[0070] The specific preparation process of a compacted segment of granite weathered residual soil aggregate solidification is as follows:

[0071] 1. Add 200g of sodium silicate to 600g of deionized water, then pour in 700g of thermally activated modified granite weathered residual soil and stir for 25min to obtain a granite weathered residual soil polymer slurry;

[0072] 2. Add 8.5 kg of construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 25 minutes to obtain loose slag slurry;

[0073] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device with a pressure value of 70 MPa and the pressure is maintained for 20 minutes;

[0074] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 20° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathered residual soil polymer solidified slag.

[0075] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that polyvinyl alcohol is not added, and the specific preparation process is as follows: The specific preparation method of thermally activated modified granite weathered residual soil and mud is as follows:

[0076] S1. Add 1 kg of granite weathering residual soil and mud into a ball mill and grind at 50 rpm for 5 h to obtain fine granite weathering residual soil and mud;

[0077] S2. 1 kg of the refined granite weathering residual soil mud obtained in step S1 is heated to 800° C. at a rate of 10° C. / min, kept warm for 2 hours, and then cooled to room temperature to obtain thermally activated granite weathering residual soil mud.

[0078] S3. 50 g of nanocellulose was added to 400 g of deionized water and stirred for 50 min, then 5 g of ammonium persulfate was added, the temperature was raised to 60 ° C and stirred for 4 h, then centrifuged, washed and dried to obtain carboxylated nanocellulose;

[0079] S4. Add 39 g of carboxylated nanocellulose and 39 g of 3-methyl-15-phenylpentadecanoic acid obtained in step S3 to 230 g of deionized water, stir for 40 min, add 1 kg of thermally activated granite weathering residual soil mud obtained in step S2, stir for 4 h, and obtain thermally activated modified granite weathering residual soil mud.

[0080] The specific preparation process of a compacted segment of granite weathered residual soil aggregate solidification is as follows:

[0081] 1. Add 200g of sodium silicate to 600g of deionized water, then pour in 700g of thermally activated modified granite weathered residual soil and stir for 25min to obtain a granite weathered residual soil polymer slurry;

[0082] 2. Add 8.5 kg of construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 25 minutes to obtain loose slag slurry;

[0083] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device with a pressure value of 70 MPa and the pressure is maintained for 20 minutes;

[0084] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 20° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathered residual soil polymer solidified slag.

[0085] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that 3-methyl-15-phenylpentadecanoic acid is not added, and the specific preparation process is as follows: The specific preparation method of the modified granite weathering residual soil and mud is as follows:

[0086] S1. Add 1 kg of granite weathering residual soil and mud into a ball mill and grind at 50 rpm for 5 h to obtain fine granite weathering residual soil and mud;

[0087] S2. 40 g of nanocellulose was added to 346.5 g of deionized water and stirred for 40 min, then 4 g of ammonium persulfate was added, the temperature was raised to 55 ° C and stirred for 3 h, then centrifuged, washed and dried to obtain carboxylated nanocellulose;

[0088] S3. Add 77g of polyvinyl alcohol and 38.5g of carboxylated nanocellulose to 385g of deionized water and stir for 40min, add 2.3g of 98% sulfuric acid, heat to 70°C with stirring, react for 7h, adjust the pH to neutral, filter, wash and dry to obtain modified polyvinyl alcohol.

[0089] S4. 1 kg of the refined granite weathering residual soil mud obtained in step S1 is heated to 800° C. at a rate of 10° C. / min, kept warm for 2 hours, and then cooled to room temperature to obtain thermally activated granite weathering residual soil mud.

[0090] S5. Add 77g of modified polyvinyl alcohol obtained in step S3 to 230g of deionized water, stir for 40min, add 1Kg of thermally activated granite weathering residual soil mud obtained in step S4, stir for 4h, and obtain thermally activated modified granite weathering residual soil mud.

[0091] The specific preparation process of a compacted segment of granite weathered residual soil aggregate solidification is as follows:

[0092] 1. Add 200g of sodium silicate to 600g of deionized water, then pour in 700g of modified granite weathering residual soil and stir for 25min to obtain a granite weathering residual soil polymer slurry;

[0093] 2. Add 8.5 kg of construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 25 minutes to obtain loose slag slurry;

[0094] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device with a pressure value of 70 MPa and the pressure is maintained for 20 minutes;

[0095] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 20° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathered residual soil polymer solidified slag.

[0096] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that 3-methyl-15-phenylpentadecanoic acid is replaced by 3-methylhexadecanoic acid, and the specific preparation process is as follows: The specific preparation method of thermally activated modified granite weathering residual soil and mud is as follows:

[0097] The specific preparation method of thermally activated modified granite weathered residual soil and mud is as follows:

[0098] S1. Add 1 kg of granite weathering residual soil and mud into a ball mill and grind at 50 rpm for 5 h to obtain fine granite weathering residual soil and mud;

[0099] S2. 40 g of nanocellulose was added to 346.5 g of deionized water and stirred for 40 min, then 4 g of ammonium persulfate was added, the temperature was raised to 55 ° C and stirred for 3 h, then centrifuged, washed and dried to obtain carboxylated nanocellulose;

[0100] S3. 77 g of polyvinyl alcohol, 38.5 g of carboxylated nanocellulose and 38.5 g of 3-methylhexadecanoic acid were added to 385 g of deionized water and stirred for 40 min, 2.3 g of 98% sulfuric acid was added, the temperature was raised to 70 ° C with stirring, the reaction was carried out for 7 h, the pH was adjusted to neutral, filtered, washed and dried to obtain modified polyvinyl alcohol.

[0101] S4. 1 kg of the refined granite weathering residual soil mud obtained in step S1 is heated to 800° C. at a rate of 10° C. / min, kept warm for 2 hours, and then cooled to room temperature to obtain thermally activated granite weathering residual soil mud.

[0102] S5. Add 77g of modified polyvinyl alcohol obtained in step S3 to 230g of deionized water, stir for 40min, add 1Kg of thermally activated granite weathering residual soil mud obtained in step S4, stir for 4h, and obtain thermally activated modified granite weathering residual soil mud.

[0103] The specific preparation process of a compacted segment of granite weathered residual soil aggregate solidification is as follows:

[0104] 1. Add 200g of sodium silicate to 600g of deionized water, then pour in 700g of thermally activated modified granite weathered residual soil and stir for 25min to obtain a granite weathered residual soil polymer slurry;

[0105] 2. Add 8.5 kg of construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 25 minutes to obtain loose slag slurry;

[0106] 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device with a pressure value of 70 MPa and the pressure is maintained for 20 minutes;

[0107] 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 20° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathered residual soil polymer solidified slag.

[0108] Performance Testing

[0109] 1. Final setting time test: Pour the loose slag slurry prepared according to the raw material composition of Examples 1-3 and Comparative Examples 1-4 into a test mold, scrape the surface, insert a Vicat needle into the cement slurry, and the time when the needle tip cannot completely penetrate the cement slurry is the final setting time. Each group of tests is tested three times and the average value is taken. The experimental data are shown in Table 1.

[0110] 2. Unconfined compressive strength test: A compacted segment of granite weathered residual soil polymer solidified slag prepared according to the raw material composition of Examples 1-3 and Comparative Examples 1-4 was prepared into a cylinder with a height of 100 mm and a diameter of 100 mm in a standard test mold, and cured in a curing box at 20°C and a humidity of 95% for 28 days. The sample that has expired for curing was taken out of the curing box, and the appearance of the sample was checked to see if it was intact. The sample was placed at the center of the lower pressure plate of a microcomputer-controlled electronic universal testing machine. After adjusting the position, an axial pressure was applied to the sample at a loading rate of 1 mm / min until the sample was destroyed. The maximum load value when the sample was destroyed was recorded, and the unconfined compressive strength was calculated according to the formula, where the strength is equal to the failure load divided by the cross-sectional area of ​​the sample. The experimental data are shown in Table 1.

[0111] 3. Water stability coefficient test: A granite weathering residual soil polymer solidification slag compaction segment prepared according to the raw material composition of Examples 1-3 and Comparative Examples 1-4 was prepared into a cylinder with a height of 100 mm and a diameter of 100 mm in a standard test mold, and cured in a curing box at 20°C and a humidity of 95% for 28 days. The expired sample was taken out of the curing box, and the appearance of the sample was checked to see if it was intact. The cured sample was completely immersed in water at room temperature for 24 hours. After the immersion was completed, the test piece was taken out, the surface moisture was wiped off, and the sample was placed at the center of the lower pressure plate of a microcomputer-controlled electronic universal testing machine. After adjusting the position, axial pressure was applied to the sample at a loading rate of 1 mm / min until the sample was destroyed. The unconfined compressive strength of each sample was recorded, and the water stability coefficient Cw was calculated according to the formula: Cw=Rw / Rd×100%, wherein Rw is the compressive strength after immersion, and Rd is the compressive strength tested in the unconfined compressive strength test. The experimental data are shown in Table 1.

[0112] Table 1 Experimental results

[0113] Final setting time / min Unconfined compressive strength / MPa Water stability coefficient / % Example 1 40 35.8 97.03 Example 2 35 37.1 98.10 Example 3 37 36.7 97.65 Comparative Example 1 47 33.8 92.42 Comparative Example 2 51 29.7 94.14 Comparative Example 3 45 30.4 88.29 Comparative Example 4 44 31.7 93.58

[0114] Data analysis: It can be seen from Examples 1-3 in Table 1 that the compacted granite weathered residual soil polymer-solidified slag segments prepared by the method for preparing compacted granite weathered residual soil polymer-solidified slag segments of the present invention have rapid coagulation ability and excellent unconfined compressive strength. At the same time, when immersed in water for a long time, they can still maintain good stability and are not prone to collapse.

[0115] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the carboxylated nanocellulose used in the present invention is of great help in reducing the setting time, improving the unconfined compressive strength and increasing the water stability. This may be because the carboxylated nanocellulose can undergo an esterification reaction with polyvinyl alcohol to firmly combine together. During the curing process of the material, the carboxylated nanocellulose can better interact with other components to accelerate the reaction process, while ordinary nanocellulose lacks this promoting effect, resulting in a slower reaction and an increase in the final setting time; in improving the unconfined compressive strength, the carboxylated nanocellulose can be combined with other components by chemical means to play a role, while ordinary nanocellulose can only participate in it by physical blending. The nanocellulose has a weak binding force with other components and cannot play a good role, resulting in a decrease in the unconfined compressive strength; the chemical cross-linked structure formed by the carboxylated nanocellulose and polyvinyl alcohol may also improve the strength and water resistance of the material to a certain extent, and ordinary nanocellulose cannot form such a cross-linked structure, resulting in poor water stability.

[0116] It can be seen from Example 2 and Comparative Example 2 in Table 1 that when polyvinyl alcohol is not added, various properties of the segment are greatly affected. This may be because the lack of polyvinyl alcohol makes it impossible to produce a cross-linked structure with the heat-activated modified granite weathering residual soil and mud. At the same time, the carboxylated nanocellulose lacks the hydroxyl group provided by polyvinyl alcohol and has no suitable grafting site, so it cannot be combined with the heat-activated modified granite weathering residual soil and mud by chemical methods, resulting in a longer setting time of the segment and a decrease in the unconfined compressive strength. In addition, polyvinyl alcohol can improve the reactivity of the material system and promote chemical reactions between other components. In the absence of polyvinyl alcohol, the overall reaction rate is reduced, resulting in poor curing effect of the material, which in turn affects the water stability.

[0117] It can be seen from Example 2 and Comparative Example 3 in Table 1 that the addition of 3-methyl-15-phenylpentadecanoic acid plays a beneficial role in the entire material system. This may be because the long-chain structure of 3-methyl-15-phenylpentadecanoic acid itself can be cross-linked and entangled with materials such as polyvinyl alcohol to accelerate the curing process of the material, and because of the presence of the benzene ring, it can enhance the mechanical properties of the material as a rigid group. At the same time, the long-chain structure is hydrophobic, which can reduce the absorption of water by the material, thereby improving the water resistance of the material.

[0118] It can be seen from Example 2 and Comparative Example 4 in Table 1 that when the benzene ring structure is missing, the final setting time of the segment will be extended, the unconfined compressive strength will be reduced, and the water stability will be worse. This may be because the benzene ring increases the chemical cross-linking sites and reaction activity, accelerates the curing process of the material, and shortens the final setting time. The benzene ring structure can also improve the dispersibility of the granite weathering residual soil and mud, making it more evenly distributed in the material system and forming a denser microstructure. This dense structure helps to improve the overall strength of the material. The benzene ring structure is hydrophobic and can reduce the material's absorption of water. Although the long-chain structure has a certain degree of hydrophobicity, it lacks the additional hydrophobic effect of the benzene ring, resulting in increased absorption of water by the material and reduced water stability.

[0119] It should be understood by those skilled in the art that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A granite weathering residual soil aggregate solidification slag compaction section, characterized in that The raw material composition and mass percentage of this section are: thermally activated modified granite weathered residual soil 5.26%-8.31%, sodium silicate 1.21%-2.86%, deionized water 4.26%-8.18%, engineering slag 80.98%-89.15%; The specific preparation method of the thermally activated modified granite weathered residual soil and mud is as follows: S1. Add the granite weathering residual soil and mud into a ball mill and grind at 40-60rpm for 4-6h to obtain fine granite weathering residual soil and mud; S2. Mix the nanocellulose, ammonium persulfate and deionized water, heat to 50-60°C, stir for 2-4h, centrifuge, wash and dry to obtain carboxylated nanocellulose; S3. The polyvinyl alcohol, carboxylated nanocellulose, 3-methyl-15-phenylpentadecanoic acid and deionized water were mixed, a catalyst was added, the temperature was raised to 60-80°C with stirring, the reaction was carried out for 6-8h, the pH was adjusted to neutral, the mixture was filtered, washed and dried to obtain modified polyvinyl alcohol; S4. The refined granite weathering residual soil mud obtained in step S1 is heated to 700-900°C at a rate of 5-15°C / min, kept warm for 1-3h, and then cooled to room temperature to obtain thermally activated granite weathering residual soil mud; S5. The modified polyvinyl alcohol obtained in step S3 is mixed with deionized water, stirred for 30-50 min, and the thermally activated granite weathering residual soil mud obtained in step S4 is added, and stirred for 3-5 h to obtain thermally activated modified granite weathering residual soil mud.

2. The granite weathering residual soil aggregate solidification slag compaction segment according to claim 1, characterized in that: The solidified soil compaction segment is in the shape of a cylinder or a prism.

3. The granite weathering residual soil aggregate solidification slag compaction segment according to claim 1, characterized in that: The sodium silicate has a modulus of 0.9-1.

5.

4. The granite weathering residual soil aggregate solidification slag compaction segment according to claim 1, characterized in that: The construction waste soil is waste soil excavated from underground construction with a particle size not exceeding 4.75 mm.

5. The granite weathering residual soil aggregate solidification slag compaction segment according to claim 1, characterized in that: The granite weathered residual soil and mud in step S1 are particles with a particle size not exceeding 0.15 mm in the granite weathered residual soil excavated during underground engineering construction.

6. The granite weathering residual soil aggregate solidification slag compaction segment according to claim 1, characterized in that: In step S2, the weight ratio of nanocellulose, ammonium persulfate and deionized water is 0.5-1:0.05-0.1:5-8.

7. The granite weathering residual soil aggregate solidification slag compaction segment according to claim 1, characterized in that: In step S3, the weight ratio of polyvinyl alcohol, carboxylated nanocellulose, 3-methyl-15-phenylpentadecanoic acid and deionized water is 0.8-1.2:0.4-0.6:0.4-0.6:3.2-7.2, and the catalyst refers to sulfuric acid with a concentration of 98%.

8. The granite weathering residual soil aggregate solidification slag compaction segment according to claim 1, characterized in that: In step S5, the weight ratio of modified polyvinyl alcohol, deionized water and thermally activated granite weathered residual soil and mud is 0.25-0.8:1-2.4:5-8.

9. The method for preparing a compacted segment of granite weathered residual soil aggregate solidification according to any one of claims 1 to 8, characterized in that: The following steps are involved:

1. After adding sodium silicate to deionized water, pour in the thermally activated modified granite weathering residual soil and mud and stir for 20-30 minutes to obtain the granite weathering residual soil polymer slurry; 2. Add construction slag to the granite weathering residual soil aggregate slurry obtained in step 1, and stir for 20-30 minutes to obtain loose slag slurry; 3. The loose slag slurry obtained in step 2 is loaded into a steel mold, and then a steel pressure head is placed on the slag slurry to compact the loose slag slurry by the weight of the pressure head; then the slag slurry in the mold is compacted using a pressure device, the pressure value is 65-75MPa, and the pressure is maintained for 10-30min; 4. The steel mold is disassembled, and the compacted solidified slag segment is taken out, and is placed in an environment with a temperature of 17-23° C. and a relative humidity of more than 95% for curing for 28 days to obtain a compacted segment of granite weathering residual soil polymer solidified slag.

Citation Information

Patent Citations

  • A steel tube concrete column with built-in compacted cement soil segment and construction method thereof

    CN115627877B

  • Refuse-soil geopolymer solidifying material and preparation method thereof

    CN106810090A

  • Residue soil baking-free brick prepared from high-temperature modified residual mud and preparation method of residual soil baking-free brick

    CN115259764A

  • Perlite-based high-strength composite insulation board and preparation method thereof

    CN117417174A

  • Low-fiber-content high-ductility geopolymer concrete based on engineering residue soil and preparation method thereof

    CN117843300A